Antibacterial activities of terminalia catappa leaves againsts streptococcus sp. in tilapia disease / Noorshilawati Abdul Aziz …[et al.] - Abdul Aziz, Noorshilawati; Baharuddin, Nurul Aida Fatihah; Abdullah, Nur Suraya; Rosli, Fazidah; Mohammed, Anisah; Yusop, Mohamad Amir Shah (2013)
This study was conducted to evaluate the antibacterial activity of Terminalia catappa leaves extract against Streptococcus sp. on Tilapia fish disease. The leaves extracts used were hexane, chloroform, methanol and aqueous extracts at different concentration of 50 mg/ml, 100mg/ml, 500mg/ml, 1000mg/ml and 1500mg/ml. The disc diffusion method used to screening the antibacterial activity against Streptococcus sp. The inhibition zone used to measure the antibacterial activity. Result found that all the extracts showed the antibacterial activity. However, the extracts (hexane, chloroform and aqueous) at 50 mg/ml do not showed any inhibition. T catappa methanol extract showed to be the best antibacterial agent against Streptococcus sp. with inhibition zone measured 22.67 mm. Based on the finding it can be concluded that Terminalia catappa leaves extract have antibacterial activities against Streptococcus sp. on Tilapia fish disease.